Emerging soil contamination by hexamethylene and toluene diisocyanates in China: Distribution characteristics and influencing factors - Xiaomu Cao; Xuelong Cao; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Yuqing Liang; Yongming Luo; Defu He (Environmental Pollution, 2026)

Evaluation of Rice Yield Attributes, Loach Muscle Quality, and Soil Biochemical Composition Under Rice–Loach Coculture System - Chuanqi Yu; Wenlu Zhu; Wenjun Wang; Wenqiang Xu; Yu Liu; Xingtian Cai; Yanfa Xu; Defu Yang; Zhuqing Yang; Zirui Wang; Qiubai Zhou; Haohua He (Fishes, 2026)
This study aimed to evaluate rice yield attributes, loach Paramisgurnus dabryanus muscle quality, and soil biochemical composition under rice monoculture (RM), rice–loach coculture (RLC), and loach monoculture (LM). This trial was conducted for 90 days, and then rice, fish muscle and soil were obtained for analyses. The results showed that there were no significant differences in rice yield attributes between the rice–loach coculture (RLC) and rice monoculture (RM) groups. However, rice–loach coculture (RLC) improved muscle quality-related parameters, including increased hardness and springiness of loach muscle. Meanwhile, muscle metabolomic analysis showed that all the differentially expressed metabolites (DEMs) in the significantly enriched pathways of lysine degradation and lysine biosynthesis were up-regulated in the rice–loach coculture (RLC) group compared with the loach monoculture (LM) group. Furthermore, the rice–loach coculture (RLC) improved soil physicochemical properties, including an increase in microbial biomass nitrogen (MBN) content and activities of soil N-acquiring enzymes (NAG and LAP). Moreover, soil microbiome analysis showed that the abundance of Candidatus Koribacter versatilis, Acidobacteria bacterium WX27 and Pseudolabrys taiwanensis was significantly increased in the rice monoculture (RM) and rice–loach coculture (RLC) groups compared with the loach monoculture (LM) group. Pairwise Spearman’s correlation analysis of the top 30 soil microbial species and soil physicochemical properties indicated that Terrimonas sp. H1YJ31 showed a highly significant positive correlation with the soil N-acquiring enzymes (N-acetylglucosaminidase, NAG; leucine aminopeptidase, LAP) and a soil C-acquiring enzyme (exo-β-1,4-glucanase C1), whereas Gaiella occulta, Methyloceanibacter marginalis and Anaerohalosphaera lusitana had a highly significant negative correlation with S-NAG, S-LAP and S-C1. In short, the improved fish muscle quality and soil biochemical composition were ascribed to the increased hardness and springiness of loach muscle and the abundance of soil Terrimonas sp. H1YJ31.

Zinc-reinforced sandwich-structured nano-magnesium oxide composite collagen barrier membrane for promoting bone regeneration - Hong Du; Shasha Lei; Jianhui Wu; Yiruo He; Lun Yuan; Liming Ge; Changdao Mu; Zhilang Xu; Defu Li (Chemical Engineering Journal, 2026)

Manipulation of autophagy regulates mitochondrial homeostasis and early embryo development of cryopreserved porcine oocytes - Jiehuan Xu; Mengqian He; Jun Gao; Lingwei Sun; Caifeng Wu; Shushan Zhang; Defu Zhang; Jianjun Dai (Animal Reproduction Science, 2026)

Policy-driven distinct dust pollution patterns in a super-large magnesite mining area: Spatiotemporal analysis integrating satellite remote sensing and CALPUFF model - Baodong Ma; Ting Kang; Shuxian Gao; Shuai He; Defu Che; Yuansheng Zhang (Journal of Cleaner Production, 2026)

Effect of palladium loading on catalytic performance and product selectivity during diclofenac degradation by Pd0@anaerobic activated sludge - Xiaodi Li; Jingzhou Zhou; Lin Yang; Si Pang; Yi Yang; Defu Gan; Junxia He; Penghui Shi; Siqing Xia (Journal of Cleaner Production, 2026)

Two-phase structure matching strategy promotes formation of built-in electric fields in Eu-Co3O4/NiFe LDH heterojunction for anion exchange membrane water electrolysis - Wenjun Zhang; Xiaohui He; Jian Huang; Defu Chen (Chemical Engineering Journal, 2026)

Soil fauna Protaetia brevitarsis mediated polyethylene microplastic biodegradation - Jie Jiang; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Xuelong Cao; Wei-Min Wu; Defu He (Science of The Total Environment, 2025)

Earthworms multifacetedly drive size- and type-dependent microplastic transport in soils - Xiaoting Zhang; Yan Liu; Defu He (Environmental Pollution, 2025)

Simultaneous hydroxyapatite-based phosphorus recovery and partial denitrification-anammox-based nitrogen removal during sludge leachate treatment - Ben Dai; Yifeng Yang; Zuobin Wang; Jingzhou Zhou; Xiaodi Li; Yi Yang; Defu Gan; Junxia He; Xin Zhang; Siqing Xia (Journal of Water Process Engineering, 2024)

Effects of dietary Allium mongolicum Regel powder supplementation on the growth performance, meat quality, antioxidant capacity and muscle fibre characteristics of fattening Angus calves under heat stress conditions - Wangjing Liu; Huixia Gao; Jianjian He; Aihuan Yu; Chenxu Sun; Yaodi Xie; Haibo Yao; He Wang; Yueyan Duan; Jinsheng Hu; Defu Tang; Tao Ran; et al. (Food Chemistry, 2024)

Soil microplastic analysis: a harmonized methodology - Piumi Amasha Withana; Sachini Supunsala Senadheera; Defu He; Michael S. Bank; Cheng Gu; Sung Yeon Hwang; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2024)

Algae polysaccharide-induced transport transformation of nanoplastics in seawater-saturated porous media - Changjian Luo; Yuanzhang Hou; Wenkai Ye; Yuchen Tang; Defu He; Liwen Xiao; Yuping Qiu (Water Research, 2024)

Soil-dwelling grub larvae of Protaetia brevitarsis biodegrade polystyrene: Responses of gut microbiome and host metabolism - Jie Jiang; Haowen Xu; Xiaomu Cao; Yuqing Liang; Aoyun Mo; Xuelong Cao; Yan Liu; Mark Eric Benbow; Craig S. Criddle; Wei-Min Wu; Defu He (Science of The Total Environment, 2024)

Biogenic palladium nanoparticles for wastewater treatment: Formation, applications, limitations, and future directions - Xiaodi Li; Lin Yang; Jingzhou Zhou; Ben Dai; Defu Gan; Yi Yang; Zhenyu Wang; Junxia He; Siqing Xia (Journal of Water Process Engineering, 2024)

Polymer chain extenders induce significant toxicity through DAF-16 and SKN-1 pathways in Caenorhabditis elegans: A comparative analysis - Aoyun Mo; Yuqing Liang; Xiaomu Cao; Jie Jiang; Yan Liu; Xuelong Cao; Yuping Qiu; Defu He (Journal of Hazardous Materials, 2024)

Removal of microplastics from water by coagulation of cationic-modified starch: An environmentally friendly solution - Wei Gao; Aoyun Mo; Jie Jiang; Yuqing Liang; Xiaomu Cao; Defu He (Science of The Total Environment, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Polystyrene nanospheres-induced hepatotoxicity in swamp eel (Monopterus albus): From biochemical, pathological and transcriptomic perspectives - Weiwei Lv; Haotian Gu; Defu He; Zhiquan Liu; Chunxia Yao; Weiwei Huang; Quan Yuan; Wenzong Zhou (Science of The Total Environment, 2023)

DNA origami-mediated plasmonic dimer nanoantenna-based SERS biosensor for ultrasensitive determination of trace diethylstilbestrol - Sen Li; Baodi Shi; Defu He; Huanying Zhou; Zhixian Gao (Journal of Hazardous Materials, 2023)

Microfiber-loaded bacterial community in indoor fallout and air-conditioner filter dust - Yingxin Chen; Xinyu Li; Wei Gao; Yalin Zhang; Aoyun Mo; Jie Jiang; Defu He (Science of The Total Environment, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

Prominent toxicity of isocyanates and maleic anhydrides to Caenorhabditis elegans: Multilevel assay for typical organic additives of biodegradable plastics - Xinyu Li; Yingxin Chen; Wei Gao; Aoyun Mo; Yalin Zhang; Jie Jiang; Defu He (Journal of Hazardous Materials, 2023)

Environmental fate and impacts of biodegradable plastics in agricultural soil ecosystems - Aoyun Mo; Yalin Zhang; Wei Gao; Jie Jiang; Defu He (Applied Soil Ecology, 2023)

Filtered maximum likelihood expectation maximization based global reconstruction for bioluminescence tomography - Defu Yang; Lin Wang; Dongmei Chen; Chenggang Yan; Xiaowei He; Jimin Liang; Xueli Chen (Medical & Biological Engineering & Computing, 2018)

Chronic Exposure to Perfluorooctane Sulfonate Reduces Lifespan of Caenorhabditis elegans Through Insulin/IGF-1 Signaling - Tiantian Xu; Ping Li; Siyu Wu; Dan Li; Jingxuan Wu; Kathleen M. Raley-Susman; Defu He (Bulletin of Environmental Contamination and Toxicology, 2016)

Behavioral and physiological responses of forest musk deer (Moschus berezovskii) to experimental fawn manipulation - Wenxia Wang; Lan He; Shuqiang Liu; Torsten Wronski; Defu Hu (acta ethologica, 2016)

The change of organic matter in sewage sludge composting and its influence on the adsorption of pentachlorophenol (PCP) - Lou Liping; Liu Defu; Chen Huanyu; Chen Fang; He Yunfeng; Tian Guangming (Environmental Science and Pollution Research, 2015)

Toxicity bioassays for water from black-odor rivers in Wenzhou, China - He DeFu; Chen RuiRui; Zhu EnHui; Chen Na; Yang Bo; Shi HuaHong; Huang MinSheng (Environmental Science and Pollution Research, 2015)

Effect of Iron Plaque Formation on Phosphorus Accumulation and Availability in the Rhizosphere of Wetland Plants - Defu Xu; Jianming Xu; Yan He; P. M. Huang (Water, Air, & Soil Pollution, 2009)